Occurrence of Aetalion reticulatum (Linnaeus) (Hemiptera: Aethalionidae) on Dipteryx alata Vogel (Fabaceae) in Minas Gerais, Brazil - da Silva Souza , Jaqueline; Boscardin, Jardel (EntomoBrasilis, 2020)
The baruzeiro or baru (Dipteryx alata Vogel) is a tree species native to Brazil that is known for its production of edible nuts with high nutritional value. However, little is known about the insects associated with this forest species. Therefore, this study aims to document the occurrence of leafhoppers on baruzeiro trees in the state of Minas Gerais, southeastern Brazil. We therefore examined baruzeiro plants in an afforestation plot at the Universidade Federal de Uberlândia (18°43'33"S; 47°31'31"W) in August 2020, located in the municipality of Monte Carmelo, Minas Gerais. The leafhopper species was identified as Aetalion reticulatum (Linnaeus) (Hemiptera: Aethalionidae). The ant species Camponotus crassus Mayr (Hymenoptera: Formicidae) was found to feed on the honeydew released by leafhoppers, demonstrating facultative mutualism between the species. This is the first report of A. reticulatum on D. alata in Minas Gerais.